Empirical damage prediction in sublevel cave crosscuts at the Malmberget mine - Jones, TH; Saiang, David (Caving 2022: Fifth International Conference on Block and Sublevel Caving, 2022)
Building on the empirical research completed in the footwall contact zone of LKAB’s Malmberget mine, a method has been developed for predicting damage in the crosscut entries of the mine layout. Threedimensional stress measurements combined with analyses of measured and observed damage in the crosscuts have allowed new interpretations of the crosscut performance. Stress analysis focused on the relative differential stresses measured in the area of interest. These stress changes were then linked directly to observed changes in the entry condition according to the Entry Condition Rating (ECR) system, a damage mapping system developed for the mine. A bilinear model was used to describe the entry condition rate of change such that the peak measured differential stress corresponds to increased degradation rates. These bilinear degradation rate trends are shown to be directly related to the geotechnical qualities of the rock using the Geologic Strength Index (GSI) of the monitored locations, irrespective of lithology. The final step was to develop an empirical model that allows prediction of a crosscut’s future ECR based on changes in the relative differential stress and the GSI of the crosscut. In combination with simple numerical modelling tools the model can be used to predict ahead of time when additional reinforcement will be necessary. Funder: Luossavaara Kiirunavaara AB (406); ISBN för värdpublikation: 978-0-6450938-3-4 Design Methods for Variable Stress, Variable-Geology Environments